Long-timescale dynamics of the Drew-Dickerson dodecamer - Dans, Pablo D; Danilāne, Linda; Ivani, Ivan; Dršata, Tomáš; Lankaš, Filip; Hospital, Adam; Walther, Jürgen; Pujagut, Ricard Illa; Battistini, Federica; Gelpí, Josep Lluis; Lavery, Richard; Orozco, Modesto (Nucleic acids research, 2016)
We present a systematic study of the long-timescale dynamics of the Drew-Dickerson dodecamer (DDD: d(CGCGAATTGCGC)2) a prototypical B-DNA duplex. Using our newly parameterized PARMBSC1 force field, we describe the conformational landscape of DDD in a variety of ionic environments from minimal salt to 2 M Na(+)Cl(-) or K(+)Cl(-) The sensitivity of the simulations to the use of different solvent and ion models is analyzed in detail using multi-microsecond simulations. Finally, an extended (10 μs) simulation is used to characterize slow and infrequent conformational changes in DDD, leading to the identification of previously uncharacterized conformational states of this duplex which can explain biologically relevant conformational transitions. With a total of more than 43 μs of unrestrained molecular dynamics simulation, this study is the most extensive investigation of the dynamics of the most prototypical DNA duplex.
Keywords: chlorid draselný; Nucleic Acid Conformation; Models, Molecular; B-DNA; DNA, B-Form; molekulární modely; Molecular Dynamics Simulation; konformace nukleové kyseliny; Sodium Chloride; Potassium Chloride; simulace molekulární dynamiky; chlorid sodný